In-vitro preformulation studies for the development of a novel antidiabetic combination therapy involving linagliptin and dextromethorphan - Shishir, Tushar Ahmed (BRAC Univeristy, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.